2019
DOI: 10.31195/ejejfs.580587
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in fat and fatty acid profiles of the Sakarya Chub (Squalius pursakensis) from the Melen river basin

Abstract: In this study, total lipids and fatty acid composition of Squalius pursakensis fillet samples which were obtained from Melen River Basin during winter, spring and summer seasons were evaluated. Total lipid levels were 1.80% in winter, 2.56% in spring and 5.17% in summer. The composition of fatty acids showed that total polyunsaturated fatty acids (32.05-38.90%) were highest, followed by monounsaturated (29.85-35.40%) and saturated (27.10-31.23%). The fatty acid composition of polyunsaturated fatty acids (PUFAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
2
1
1
Order By: Relevance
“…In the study, it is found that B. tauricus's dominant SFAs are palmitic acid (C16:0), Myristic acid (C164:0) and stearic acid (C18:0) (Figure 2); dominant MUFAs are Transoleic acid (C18:1n9t), Palmitoleic acid (C16:1), Erucic acid (C22:1n9), Oleic acid (C18:1n9c), Gadoleic acid (C20:1n9); dominant PUFAs Docosahexaenoic acid (C22:6n3), Linoleic acid (C18:2n6c), Eicosapentaenoic acid (C20:5n3), Alfa linolenic acid (C18:3n3) (Table 2). In studies by Ozogul et al [35], Mahmoud et al [36], Hisar and Hisar [37] on Cyprinus carpio, by Inan et al [24] on S. pursakensis and by Ates [28] on Squalius pursakensis and Capoeta, dominant SFAs were determined as myristic, palmitic and stearic acid, similar to our study. In studies by Gokce et al [38] Solea solea has palmitic (19.00%) and stearic acid (6,91%) rates at most in summer, while in our study, palmitic (17.64%) and stearic acid (6.93%) rates were found at most in spring.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the study, it is found that B. tauricus's dominant SFAs are palmitic acid (C16:0), Myristic acid (C164:0) and stearic acid (C18:0) (Figure 2); dominant MUFAs are Transoleic acid (C18:1n9t), Palmitoleic acid (C16:1), Erucic acid (C22:1n9), Oleic acid (C18:1n9c), Gadoleic acid (C20:1n9); dominant PUFAs Docosahexaenoic acid (C22:6n3), Linoleic acid (C18:2n6c), Eicosapentaenoic acid (C20:5n3), Alfa linolenic acid (C18:3n3) (Table 2). In studies by Ozogul et al [35], Mahmoud et al [36], Hisar and Hisar [37] on Cyprinus carpio, by Inan et al [24] on S. pursakensis and by Ates [28] on Squalius pursakensis and Capoeta, dominant SFAs were determined as myristic, palmitic and stearic acid, similar to our study. In studies by Gokce et al [38] Solea solea has palmitic (19.00%) and stearic acid (6,91%) rates at most in summer, while in our study, palmitic (17.64%) and stearic acid (6.93%) rates were found at most in spring.…”
Section: Discussionsupporting
confidence: 89%
“…The reason B. tauricus's total lipid amounts are low in winter is thought to be due to an increase in lipid usage by fishes needing more energy during the winter season. For poikilotherm creatures, the temperature is the most crucial factor affecting fish-feeding activity [24]. Similar results (in winter, 1.19%) were found in a study on the species Dicentrarchus labrax by Belikusakli [25].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations